2019
DOI: 10.5713/ajas.19.0486
|View full text |Cite
|
Sign up to set email alerts
|

Research advances in reproduction for dairy goats

Abstract: Considerable progress in reproduction of dairy goats has been made, with advances in reproductive technology accelerating dairy goat production since the 1980s. Reproduction in goats is described as seasonal. The onset and length of the breeding season is dependent on various factors such as breed, climate, physiological stage, male effect, breeding system, and photoperiod. The reproductive physiology of goats was investigated extensively, including hypothalamic and pituitary control of the ovary related to es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 91 publications
0
33
1
1
Order By: Relevance
“…Lipase, an important inhibitory factor of sperm viability and cryopreservation, is secreted from the bulbourethral gland in goats but not in other livestock [ 6 ]. Several studies have investigated the cryopreservation of black goat semen and have shown the survival rate of sperm was ranges from 60% to 65% [ 21 ], in semen by AI. The present study also found 64.2 ± 7.9 % sperm motility in frozen-thawed semen ( Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lipase, an important inhibitory factor of sperm viability and cryopreservation, is secreted from the bulbourethral gland in goats but not in other livestock [ 6 ]. Several studies have investigated the cryopreservation of black goat semen and have shown the survival rate of sperm was ranges from 60% to 65% [ 21 ], in semen by AI. The present study also found 64.2 ± 7.9 % sperm motility in frozen-thawed semen ( Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our studies on estrus synchronization has been imposing the optimum protocols to enable favorable synchrony and fertility in Korean black goats, there by generating and introducing simple, practical, and reliable methods for the commercial as well as subsistent farmers. Usually in the commercial goat industry, FSH+CIDR or PMSG+CIDR are most commonly used as effective protocols for estrus synchronisation or superovulation [ 21 ]. In ruminants, the estrus cycle can be synchronized via the insertion of a P4-impregnated intravaginal device, such as CIDR united with eCG [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…These reports show that the laparoscopic technique allows to perform different kinds of operation in a short time, especially in small ruminants. The shortening of the time of surgery in consecutive sessions (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17) was the result of the increasing skills and better cooperation of surgeons. These observations were also noticed by other authors [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…Endoscopic methods are used in breeding animals for recovering and transferring embryos, for intra-uterine insemination, and for diagnostic purposes, e.g., ovary and uterus evaluation, ovulation observation and development of corpus luteum, and oocyte recovery [1][2][3]. An increasing interest in non-surgical methods of oocyte recovery, as well as recovery and transfer of embryos for research purposes and practical implementation can be seen [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation